PENGARUH PROFITABILITAS, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR TEKNOLOGI YANG TERDAFTAR DI BEI - Titin Ariani Togatorop; Muhammad Asrin Jazuli; Ilham H Napitupulu (Jurnal Akuntansi dan Bisnis, 2026)
This study aims to analyze the effect of profitability, leverage, and firm size on firm value in the technology sector. The research method is quantitative with secondary data in the form of annual financial reports of technology companies listed on the IDX for the period 2022–2024. The sample was determined through purposive sampling, resulting in 31 companies with a three-year observation period and a total of 93 data points. The analysis used descriptive statistics and multiple linear regression with the help of SPSS version 29. The results of the study show that leverage affects firm value, while profitability and firm size have no significant effect.